Social Adjustment and Relevancy for Physical Education: - (Journal of Advances and Scholarly Researches in Allied Education, 2022)
School principal’s play an important role in creating an educational climate that provides opportunities for interaction with others. Attitude means, having a feeling about something or an opinion whether it is positive or negative. Or it is a conscious or unconscious physical posture that is displayed while interacting with others.The purpose of the study was to find the effectiveness of the principal’s attitude towards Physical Education in colleges of University of Kanpur. The subjects were 10 principals working in different colleges of University of Kanpur, for collection of data the self-made questionnaire was used. The administered questionnaire comprised of Physical Education program under which 20 statements formed to the Likert’s Scale of Strongly Agree, Agree, Undecided, Disagree and Strongly Disagree were included. The level of significance was set at 0.05. The data was analysed by using the Descriptive Technique in term of the Frequency Percentage for Likert’s Scale responses and to examine the divergence in the attitude the Chi Square Test (X2) was applied on the Likert’s Scale responses. The result shows that the Subjects (Principals) felt that the Physical activities improve the social experience in the student, Physical education events make a student more outgoing, Participating in physical activity is an aesthetic experience for the student, and active catharsis is the emotional release a person has while participating in strenuous physical activity.